2022
DOI: 10.3233/atde220196
|View full text |Cite
|
Sign up to set email alerts
|

Considering Sustainability in Reconfigurable Manufacturing Systems Research – A Literature Review

Abstract: Reconfigurable manufacturing systems (RMS) have since the introduction almost two decades ago been recognized as the future of manufacturing. In line with a rapidly increasing customer demand for mass customization, RMS have been found to be a solution for managing frequent product introductions whilst keeping a high production efficiency. However, in recent years the focus has partly shifted from producing solely from an economic standpoint towards establishing a triple bottom line of sustainability, i.e., ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Agility to changing requirements is critical for the success of a product development (PD) project and production should be capable of handling varied demand levels (Santos et al, 2017) and assets are needed to support manufacturers (Wiesner et al, 2018). Future product development can raise challenges for manufacturers such as balancing carryover or legacy systems and new systems and embracing circularity and sustainability (Isaksson and Eckert, 2020), increasing the need for flexible and reconfigurable manufacturing systems (Skärin et al, 2022). Tools are needed to provide a common language between the product and production domains to communicate their requirements (Ferreira et al, 2021).…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agility to changing requirements is critical for the success of a product development (PD) project and production should be capable of handling varied demand levels (Santos et al, 2017) and assets are needed to support manufacturers (Wiesner et al, 2018). Future product development can raise challenges for manufacturers such as balancing carryover or legacy systems and new systems and embracing circularity and sustainability (Isaksson and Eckert, 2020), increasing the need for flexible and reconfigurable manufacturing systems (Skärin et al, 2022). Tools are needed to provide a common language between the product and production domains to communicate their requirements (Ferreira et al, 2021).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The product development process is a complex engineering process that involves different disciplines and emergent behaviour (Simpson and Martins, 2011). Factors such as high product variety, uncertainty in markets, shorter lead time and sustainable manufacturing leading to reconfigurable and changeable manufacturing systems have necessitated coordinated decision-making between design and production domains (Brunoe et al, 2020;Skärin et al, 2022). Integrated product development supports interaction between product and production domains throughout the product lifecycle (Albers et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of previous academic research within circular and reconfigurable machining systems, Skärin et al [10] concluded that circularity in reconfigurable systems has thus far primarily involved adapting the systems to fit in a remanufacturing practice. Similarly, Bockholt et al [11] conducted a case study and provided empirical insights regarding the application of changeability and reconfigurable manufacturing system in order to overcome challenges in closed-loop manufacturing systems, in particular for reverse flow of products.…”
Section: Reconfigurabilitymentioning
confidence: 99%
“…Nachhaltigkeitsstrategien mit Blick auf unterschiedliche Aspekte, wie CO2-Zertifikate oder die Entkopplung des wirtschaftlichen Wachstums vom Ressourcenverbrauch sind derzeit wichtiger denn je [1]. Die Lebensdauer von Produkten, Baugruppen und Komponenten durch Kreislaufwirtschaft zu verlängern, kann dabei ein wertvoller Beitrag zur Bewältigung der Herausforderung zunehmender Nachfrage bei gleichzeitiger Ressourcenverknappung sein [2].…”
Section: Einleitung Und Problemstellungunclassified